2017
DOI: 10.1007/s00268-017-4123-3
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta‐Analysis of Laparoscopic Versus Open Appendicectomy in Adults with Complicated Appendicitis: an Update of the Literature

Abstract: LA appears to have significant benefits with improved morbidity compared to OA in complicated appendicitis (level of evidence II).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
67
3
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(84 citation statements)
references
References 61 publications
(130 reference statements)
7
67
3
7
Order By: Relevance
“…Given the frequency of appendicitis, readmission has significant cost implications and the surgical community are increasingly recognizing the need to measure and improve outcomes . This meta‐analysis is one of the first to look at readmission, as previous meta‐analyses of patients undergoing appendectomy and appendicitis have focused on diagnosis, and surgical approaches, such as laparoscopic versus open techniques . While there may be a role for conservative management in some clinical situations, most patients currently will undergo surgery rather than non‐operative management of their appendicitis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the frequency of appendicitis, readmission has significant cost implications and the surgical community are increasingly recognizing the need to measure and improve outcomes . This meta‐analysis is one of the first to look at readmission, as previous meta‐analyses of patients undergoing appendectomy and appendicitis have focused on diagnosis, and surgical approaches, such as laparoscopic versus open techniques . While there may be a role for conservative management in some clinical situations, most patients currently will undergo surgery rather than non‐operative management of their appendicitis.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that a laparoscopic approach to appendectomy was associated with fewer readmissions than with open surgery. A recent meta‐analysis of laparoscopic versus open appendectomy in adults with complicated appendicitis identified three randomized control trials and 24 case–control trials which, despite average methodological quality and low statistical heterogeneity, showed no significant difference in intra‐abdominal abscess rate with those undergoing laparoscopic approach . While operating time may be longer with a laparoscopic approach, the laparoscopic group had less surgical site infections and reduced time to resuming oral intake.…”
Section: Discussionmentioning
confidence: 99%
“…The highest predictors of post‐operative SSI were seen in individuals who had an open operation, and those who identified as ATSI. Evidence from multiple studies has demonstrated higher rates of SSI in patients who have an open compared to laparoscopic appendicectomy . Further subgroup analysis in our patient population showed that 69% of the converted to open cases were associated with complicated appendicitis.…”
Section: Discussionmentioning
confidence: 61%
“…Complicated appendicitis, defined as the presence of acute appendicitis with peritonitis, rupture, gangrene, or intra‐abdominal abscess, accounts for 14% to 55% of all appendicitis cases . Laparoscopic treatment for uncomplicated appendicitis has already demonstrated its superiority over the open approach in terms of perioperative outcomes …”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Laparoscopic treatment for uncomplicated appendicitis has already demonstrated its superiority over the open approach in terms of perioperative outcomes. [6][7][8] The current treatment strategy for both uncomplicated and complicated appendicitis varies from emergency operations to non-operative management (NOM). NOM involves the administration of antibiotic drugs with or without percutaneous drainage and then an interval appendectomy (IA).…”
Section: Introductionmentioning
confidence: 99%